Pengaruh Kualitas Aktiva Produktif, BOPO terhadap ROA dan CAR pada BPR Kabupaten Badung - Chatarine, Alvita; Lestari, Putu Vivi (E-Jurnal Manajemen; Vol 3 No 3 (2014), 2014)
The aim of this research was to know the effect of asset quality (KAP), operating performance (BOPO) towards profitability (ROA) and capital adequacy ratio (CAR) of BPR in Badung Regency. This research had 45 samples which choosen by purposive sampling technic. This research used path analysis method. The result found that only asset quality (KAP) had  insignificant effect towards operating performance (BOPO), profitability (ROA) and capital adequacy ratio (CAR). Operating performance (BOPO) had negative significant effect towards profitability (ROA), operating performance (BOPO) had positive significant effect towards capital adequacy ratio (CAR), profitability (ROA) had positive significant effect towards capital adequacy ratio (CAR), and only operating performance (BOPO) had directly and indirectly effect through profitability towards capital adequacy ratio (CAR). Keywords: Asset Quality, Operating Performace, Profitability and Capital Adequacy Ratio